Ensuring Equity in Post-Divorce Economic Rights: A Critical Analysis of Judicial Sensitivity in the Religious Court of Padang Sidimpuan, Indonesia - Tarigan, Azhari Akmal; Nasution, Muhammad Syukri Albani; Hutagalung, Syahrial Arif; Arrazy, Syafran (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2023)
Judges are pivotal in issuing impartial decisions that advocate for women, even when they function as primary providers. This study examines the judicial sensitivity towards women as primary breadwinners within families in Padang Lawas Utara. Employing a sociological approach, the research explores the realities among the indigenous people of Padang Lawas Utara. Subsequently, it conducts a comprehensive review of five decisions from the Religious Court of Padang Sidimpuan, falling under the jurisdiction of Padang Lawas Utara. The article reveals that the judges fail to consider the wife’s familial role, especially the role of the wife as the breadwinner. They concentrate solely on the male’s capabilities and rely on evidence of the husband’s income, which proves challenging to validate. Despite the husband’s ownership of assets, including land, houses, rice fields, vehicles, and others, the judge refrains from exercising the ex officio rights to provide the wife's māḍiyah (previous alimony). This underscores the inadequacy of the judge’s sensitivity in establishing the fulfillment and protection of women’s rights, particularly in the context of post-divorce scenarios.